Effectiveness of The Cooperative Learning Model Assisted by The PhET Simulation to Improve Students’ Learning Outcomes - Muh. Asri Ilham; Muh. Amri Ilham; Melinda (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
Low student learning outcomes in static fluid topics highlight the need for innovative physics learning strategies. This study evaluates the effectiveness. of a cooperative learning model assisted by PhET simulations in improving outcomes. Using a one-group pretest-posttest design with a quantitative approach, the study involved 31 students from class XI A3 who were purposively selected. A multiple-choice test covering hydrostatic pressure, Pascal’s law, and Archimedes’ principle served as the primary instrument. Data were analyzed using the N-Gain test to measure improvement. Results showed an average score increase from 49.87 to 73.94, with an N-Gain of 0.48 (moderate category). The findings suggest that cooperative learning supported by PhET simulations is pretty effective in enhancing student learning outcomes. This study implies that integrating collaborative learning with interactive simulations can be a promising innovation in physics education.